Protestology an exploratory descriptive study on the meanings of mass demonstrations and the communication process : a multi-method qualitative approach - Babon, Jose Ryan Pido 1977-; University of the Philippines Diliman College of Mass Communication (Quezon City College of Mass Communication, University of the Philippines Diliman, 2000)
This study focused on the meanings of mass demonstrations and the communication process present. Mass demonstrations are part of the existing political set-up of our society. They have been a strong force that has brought about social and political changes. History has its own accounts of the capability of mass demonstrations. From the pre-colonization era to Spanish, American and Japanese conquest in the Philippines up to the present. Filipinos have resorted to mass demonstrations because of the firm belief that such kinds of consolidated mobilizations are the best way to assert demands. Thus, with such competence found in mass demonstrations, the need to allot research attention regarding their meanings as well as the communication process was essential and substantial. The study was primarily conducted to find out the meanings that mass demonstrations hold for their demonstrators and the manner these are conveyed to the spectators. I used the Coordinated Management of Meaning (CMM) theory by Pearce and Cronen, Osgood's Behavioral Model, Information-Integration theory by Andersen, and Noise theory incorporated into Berlo's Model of Communication as the framework of the study on the meanings of mass demonstrations and the communication process. The study had a multi-method qualitative approach. It utilized both the western and the indigenous forms of data generation. The participant-observation, interviews and focus-group discussion were employed together with the "padalaw-dalaw, patanung-tanong, pakikiramdam, pakikipaglagayang-loob." Findings of the study showed that there were varied motivations why demonstrators resorted to street protests. These were their classic interpretation of the socio-political reality as imperialistic, feudalistic and bereaucratic-capitalistic, as well as their training or education, media exposure, relationship with other people, and their experience. Because of such motivations, it was found out that demonstrators had the common expectation to attain social change. And this was the very reason why they conducted mass demonstrations. In the process, they embedded that self-concept of being progressive individuals, leftist, activists, and the like. This was the case because deliberately they conformed with the ideas and teachings of the same kind of persons like Marx, Mao, and Lenin, and others. It was found out likewise that in the process of communicating, mass demonstrations had problems that concerned with the physical locations, psychological priorities of demonstrators, environment and communication materials or texts used. Likewise, the responses of the spectators regarding the advantage of mass demonstrations were open-ended. They considered them abominable when it began to affect people negatively, on the other hand, they praised mass demonstrations when they contributed something worthwhile. Based on the results of the study, the researcher recommends that the government should lay down and maximize their strategic effort to make peace agreements with the demonstrators who labeled themselves as leftists to avoid social dichotomy and revolution. On the other hand, if the concerned tolerates mass demonstrations at a maximum level, they should persuade demonstrators to do a decent type of mass demonstrations that would not affect people adversely. Regarding communication approach of mass demonstration, it is recommended that demonstrators employ more nonverbal type of promotion and it must be mass based.
Vita.
Thesis (A.B. Communication Research)--University of the Philippines Diliman
Keywords: Protest movements -- Philippines